Pertumbuhan Tunas Mahkota Nanas (Ananas comosus (L.) Merr) Secara In Vitro Dengan Penambahan Ekstrak Tomat (Solanum lycopersicumL.) Dan Benzyl Amino Purin (BAP) - Mukarlina, Mely Angela Oktaviana, Riza Linda (Universitas Tanjungpura, 2015)
The pineapple (Ananas comosus (L.) Merr) can be propagated in vitro in order to obtain large quantities of plants and to produce plants similar to the parent using a plant growth regulator i.e.extract of tomato and BAP. The research aimed to find out the effect of tomato extract and the BAP and the best concentration for the growth of crown shoots of the pineapple (A. comosus). This research was conducted for 5 months from March to August 2015 at the Laboratory ofÂ Tissue Culture of the Aloe Vera Center Pontianak. This research used a completely randomized factorial design (CRD) with 2 treatments. The first factor was the tomato extract (0%; 5%; 10%; 15%) and the second factor BAP (0 M; 10-5 M; 10-6 M; 10-7 M). The research findings indicated that the single factor of tomato extract and BAP had no significant effect on the number of shoots and leaves. The single factor of tomato extract and BAP had a significant effect on the time for the shoot to appear. The longest time it took for the shoot to appear was 37.83 days on the treatment of the tomato extract 15%, and 36.33 days in the treatment of BAP 10-7 M.